Collaborative Action as Strategy in “Global Climate Strike” Campaign of Greenpeace Indonesia (CoverAge: Journal of Strategic Communication, 2024)
Numerous environmental Non-Government Organizations (NGOs) have led climate change campaigns. Many of these campaigns were developed in collaboration with other organizations and institutions concerned with environmental issues. As a globally affiliated environmental NGO in Indonesia, Greenpeace Indonesia actively engages in regular climate change campaigns. This study investigates Greenpeace Indonesia's use of collaborative actions as a strategy in their ‘Global Climate Strike’ campaign. Utilizing the Planning, Organizing, Actuating, and Controlling (POAC) communication strategy concept, the study explores how these collaborative actions are implemented at each stage. A qualitative research approach was employed, with data collected through in-depth interviews. The findings reveal that Greenpeace Indonesia engages in collaborative actions at every stage of POAC, involving other environmental NGOs, civil society groups, Islamic boarding schools, schools, universities, musicians, and artists in developing campaign strategies. The campaign was designed to be informal and enjoyable, featuring music festivals and talk shows, to encourage the participation of many young people.